The Risks Of Electronic Accounting Information System In The Central Bank Of Libya - Adel Mohamed Hossin; Abdullah Mohammed Ayedh (Zes Rokman Resources, 2024)
Electronic accounting information systems of systems that face many risks that may affect the achievement of the objectives of those systems are considered, due to its dependence on the computer, where the synchronization of the great development of computers and information systems with the development of information technology and the rapid spread of this information and use it electronically, and the owner of this development in the use of electronic information many risks and problems that affect the information security, whether those risks were intended or unintended (internal and external) So aim of this research to study and identify the risks that threaten the accounting information systems in the Libyan environment within the Central Bank of Libya, and investigate in the most important reasons that lead to the occurring of these risks, and to investigate the procedures that prevent the occurring of these risks and researcher will be use the special questionnaire to serve the research objectives, and depends researcher in the methodology of this study on applied study to determine the risk of accounting information for the security of information and the reasons for these risks and actions that can be taken to counter the risks of the Central Bank of Libya through the sources of books, articles and papers published in scientific journals and specialized scientific messages judicial and reports issued by the Central Bank of Libya in the past years and also by distributing questionnaire will designed for distribution to the study sample in the study population and then the researcher will be analyzed this data using a program SPSS, and the study population of the Central Bank of Libya consists, and the study sample of individuals who represent the nature of their work within the bank's relationship with the search topic, This included managers and department heads, accountants, internal auditors and the Controller General of the Central Bank of Libya, in addition to the IT department staff in the bank for achieve the goal of this the study, verification of the role of protective measures to reduce the risk of electronic accounting information systems. Keywords: The risks of electronic accounting information system